Memorandum on first steps towards the improvement of the general medical services of the nation (London : Council of the Medical Practioners' Union, 1939)
1939 1939 1930s 6 pages 6 5. IMPROVEMENT OF MEDICAL EDUCATION. (20) Medical education is controlled by the General Medical Council. It was brought into being in 1858 by the Medical Act of that year. It now contains seven members elected by registered practitioners, and thirty-two appointed by the King in Council and by examining bodies. Of the thirty-two, all but one are medical men. There is no co-ordination with the medical profession and the Council is answerable to the State alone. The educational functions of the Council are not very satisfactorily stated in the Act of 1858, or in any amending Act, but they imply that no medical man may be registered, and so enabled to hold official posts, etc., unless he has first satisfied the Council that he "possesses the knowledge and skill requisite for the efficient practice of medicine." (21) There can be no doubt at all in the eyes of any unprejudiced observer that the newly registered doctor of to-day finds himself gravely handicapped by the fact that the General Medical Council has failed to bring within his reach a system of instruction calculated adequately to fit him for his work. (22) The precise remedies needed cannot yet be ascertained in detail, but the Union has issued a separate memorandum on the steps immediately necessary. A radical reform in the constitution of the General Medical Council and an age limit for its members are obvious needs. The medical course, which usually occupies six years, cannot well be lengthened, so that there must be a reduction in specialised and detailed instruction in order to provide room for more attention to subjects of social significance. It will probably be necessary to make much more use of post-graduate instruction than at present, as also of experience akin to apprenticeship under the supervision of senior practitioners. Further than this the Union cannot go pending the investigation of the whole subject, and it is suggested that this should be done by a committee consisting of social workers, medical teachers and registered practitioners. It may be noted that the education of the nurse is even more in need of reconsideration. CONCLUSIONS. (23) In conclusion, the Union would reiterate its view that there is little practical value in wrangles about ideal systems, when all energies need to be concentrated on improvements to existing services. These are urgent, and an extension of the services is also urgent. It summarises the views contained in the foregoing Memorandum as follows :— (a) That there is great need for all persons of good will to concentrate on immediately practicable first steps towards the improvements of our general health services, without too much regard to theoretical or political considerations. (b) That of all the extensions which are undoubtedly desirable, the most urgent is the provision of general practitioner services to those who cannot now obtain them. (c) That this extension should be to the whole population. (d) That it should be financed by the State and not by individual contributions. (e) That it should, for the present, be based on the existing machinery of the National Health Insurance Acts. (f) That the pauper taint should be completely removed from all forms of medical service. (g) That all practitioners willing and able to undertake maternity work should forthwith be reassociated with this work. (h) That no midwife should cease attending any mother still suffering from the effects of parturition without seeing that such further care as may be needed is likely to be obtained. (i) That the present scope of medical education should be improved and amended in certain directions. 36/H24/38